1996
DOI: 10.1046/j.1365-2648.1996.13511.x
|View full text |Cite
|
Sign up to set email alerts
|

Culture and the self: implications for the perception of depression by Australian and Vietnamese nursing students

Abstract: The theoretical influence of self-concept on cognitive and emotional aspects of behaviour was tested in an exploratory survey of 187 Australian and Vietnamese student nurse participants. Symptoms of depression were depicted in either a family scenario or a context-free list and were rated for perceived depression utilizing the Hopkins Symptom Checklist-25 (HSCL-25). Narrative data were also obtained. Australians perceived significantly more depression than the Vietnamese who normalized the behaviours. There wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…"Not having feelings of altruism to others" (54) may also act as a deficit in social contexts. These findings reflect collective and social constructions of the self-concept (Fry & Nguyen, 1996) and the importance of connection with others and fulfillment of responsibilities that are commonly associated with positive feelings in collective cultures (Tanaka-Matsumi, 2001). kurang perhatian terhadap orang lain (no feeling of altruism to others / lack of attention to others) 56 mencari persetujuan kepada orang lain (seeking agreement to others)…”
Section: Interpretation Of Mapssupporting
confidence: 56%
See 2 more Smart Citations
“…"Not having feelings of altruism to others" (54) may also act as a deficit in social contexts. These findings reflect collective and social constructions of the self-concept (Fry & Nguyen, 1996) and the importance of connection with others and fulfillment of responsibilities that are commonly associated with positive feelings in collective cultures (Tanaka-Matsumi, 2001). kurang perhatian terhadap orang lain (no feeling of altruism to others / lack of attention to others) 56 mencari persetujuan kepada orang lain (seeking agreement to others)…”
Section: Interpretation Of Mapssupporting
confidence: 56%
“…In addition to the themes described above, there was a notable absence of themes of self-fulfillment, autonomy, and personal accomplishment that are clearly evident in Western presentations of depression (Fry & Nguyen, 1996;TanakaMatsumi, 2001). This may be attributed to the high cultural and personal value placed on an individual's role within a social context as opposed to individual achievement in Indonesia (Fry & Nguyen, 1996;Wong, Kim, Zane, Kim, & Huang, 2003).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This study revealed that the Vietnamese students believed that a "superior person" would not allow troubling thoughts or emotions to overtake his/her life. The researchers describe this belief in comparison with Australian students, who identify with Western belief systems, and do not subscribe to the notion of control over one's feelings versus seeking help for suffering (Fry & Nguyen, 1996). The results of Fry's and Nguyen's (1996) study illustrate, one way culture can affect an individual's understanding and experience of depression.…”
Section: Cultural Experience Of Depressionmentioning
confidence: 99%
“…For example, in a comparative study of Australian and Vietnamese nursing students' perceptions of depression, Fry and Nguyen (1996) found that culture and self-concept influenced the experience of depression. This study revealed that the Vietnamese students believed that a "superior person" would not allow troubling thoughts or emotions to overtake his/her life.…”
Section: Cultural Experience Of Depressionmentioning
confidence: 99%